Endoscopic innovations - Hawes, Robert H. (Endoscopy, 2013)
Overall, Digestive Disease Week (DDW) 2013 was an excellent year for endoscopic innovation. For this section, the abstracts have been divided into new technologies and new techniques. The abstracts selected for review are ones that represent material that has a reasonable chance of affecting the practice of GI endoscopy.